An Investigation on the Error Patterns in Computation of Whole Numbers Committed by Singaporean Children with Dyscalculia - Chia, Noel Kok Hwee; Tee Ng, Angie Gek (Journal of the American Academy of Special Education Professionals, 2010)
In Singapore, very little research studies have been done on children with dyscalculia and mathematics-related anomalies (also known as mathematics learning disabilities) despites its problems are widespread. The writers have chosen to work with these children identified to have difficulties with mathematics at the Learning Disabilities Center. They narrowed their focus on the error patterns in computation (i.e., addition, subtraction, multiplication, and division) of whole numbers made by these children. The rationale is that children struggling with basic arithmetical computations also have difficulty completing arithmetic problems that involve multi-steps. The underlying key factor in poor computation is the inadequate or poor concept of number sense.